Calcium oxide from Pomacea canaliculata and Babylonia spirata snails - Triayu Septiani; Nurlisa Hidayati; Risfidian Mohadi (Science and Technology Indonesia, 2017)
The preparation of CaO from golden snail (Pomacea canaliculata) and lion snail (Babylonia spirata) through decomposition at various temperature i.e 700o, 800o, 900o and 1000oC during 3 hours has been carried out. Calcium oxide from decomposition was characterized using X-Ray diffractometer. Furthermore, the characterization was continued using FT-IR spectrophotometer and determination of surface area using BET analysis. The results showed that the optimum temperature for preparation of CaO from golden snail and lion snail at 900oC with 2q values are: 32.2° , 37.4o , 54o , 64.2o , 67.3° and 32.4°, 37.5°, 67.5 °, respectively. FT-IR spectra showed characteristic vibrations for the Ca-O in the sample golden snail and lion snail combustion products at a temperature of 900oC. Ca-O absorption of golden snail samples in the wavenumber around 362.62 cm-1 and lion snail seen in wavenumber around 384.76 cm-1 indicating the presence of Ca-O vibration of the metal oxide of preparation. Golden snail and the lion snail combustion at 900oC temperature of each sample which has a surface area of 20.495 m2/g, while the lion snail 17.308 m2/g. The pore diameter of golden snail 3.753 nm and 11.319 nm of lion snail. All CaO can be categorized as mesoporous material. Keywords: golden snail, lion snail, decomposition, CaO